Enhanced modulation scheme for cognitive radio over Rayleigh fading channels using power allocation and spectrum sensing models. (24th August 2020) - Rao, B. Maheswara; Baskar, S.
Majority of the spectrum occupancy measurement has been operated in the context of cognitive radio. Measurements of spectrum occupancy are enormous in outdoor elevated points such as building roofs, balconies and towers. Even though, these mentioned measurement scenarios provide better estimation of spectral activity of the primary transmitters, in practical situations where users are not located in that high point, they cannot be considered as representative of the spectrum occupancy recognised by a cognitive radio user. Over fading channels, spectrum sensing is considered as the most important operation of cognitive radios. Fading margin and count of relays within wireless communication link plays a key role in the sensing performance. Various sensing detectors are proposed in the literature, with an assumption that the primary user is either completely present or completely absent within the observation window. By using various modulation schemes for cognitive radio over Rayleigh fading channels, this paper aims to study the effect of the primary user duty cycle on spectrum sensing performance.